PENYEBARLUASKAN PENGETAHUAN HUKUM UNTUK MENINGKATKAN KESADARAN HUKUM MASYARAKAT - Pradoto, Waluyo Slamet; Jumiati, Agatha; Risnandhi, Denny; Prasetyo, Yunio Adi (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2020)
Legal knowledge is very necessary for the creation of legal understanding and awareness of legal awareness for the community. There are several factors that can affect public legal awareness. This community service is expected to provide knowledge and understanding to the community, especially students. With knowledge and understanding of the prevailing legal rules, they will maintain their legal awareness to a higher level.